ROMANIAN AND ENGLISH FOOD PROVERBS AND IDIOMS: A CONTRASTIVE VIEW - Ionescu, Daniela Corina (Proverbium - Yearbook, 2016)
The present study is a short exploration of the cross-linguistic and cross-cultural significance of a limited class of proverbs and idi-oms, those which are thematically or lexically related to food and food stuffs, of a vital nature for human existence and ‘philosophy’ of life. The literal as well as the figurative interpretation of a set of these prov-erbs and/or idioms is discussed in semantic, lexical and pragmatic terms, with a few ethno-linguistic references to the Romanian paremia and folklore in general. The study may prove useful to paremiologists and linguists alike, if we take into consideration that proverbiality and idiomaticity bear the imprint of a people’s language, cultural history, and cognitive development. This limited selection of the proverbs and idioms of Romanian and (American) English can shed some light on the common and different tastes, priorities, and linguistic idiosyncrasies shared (or not) by the two peoples and cultures.